PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PT TRINITY AUTO DI SAMARINDA - Tika Rafid Syarifah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2019)
This study aims to test and analyze how much influence Motivation and Competence on Employee Performance at PT Trinity Auto in Samarinda. The research method used in this study was observation, interviews, questionnaires, and literature study using a Likert scale and the sample used was 63 samples. Data analysis tools used are validity test, reliability test, classic assumption test, multiple linear regression test. The results showed that motivation and competency simultaneously affect employee performance. From the results of the correlation test of 0.681 which has a strong relationship between the independent variable and the dependent variable. The results of the coefficient of determination test which among the independent variables have an effect of 68.1% while the rest are influenced by variables outside this study. From the results of this study concluded that the Competence that most influences on employee performance is seen from the results of the t test with a value of 6,055. These results can prove that competence at PT Trinity Auto has an influence on employee performance.